Triple bottom line corporate social responsibility: Social, economic, and environmental impact analysis of community-based water management program - Bidiyah Siska Fiyana (Environmental, Social, Governance and Sustainable Business, 2025)
Background: Corporate Social Responsibility (CSR) environmental programs often face challenges in demonstrating measurable social, economic, and environmental impacts. The Irrigation Volunteer Forum (Forum Relawan Irigasi/FRI) in Klaten is a community-based water management initiative supported by CSR and multi-stakeholder collaboration. This study analyzes the triple bottom line impacts of the FRI program and its contribution to creating shared value for people, planet, and profit. Methods: This qualitative case study was conducted in Juwiring Sub-district, Klaten District, Central Java, from October to December 2024. Data were collected through in-depth interviews with 25 informants, participatory observation, and document analysis. Data were analyzed using the interactive model of Miles et al. (2014). Findings: The FRI program generated positive impacts across three dimensions. Socially, it reduced conflicts in water distribution, increased trust among farmers, strengthened social solidarity, and improved institutional capacity. Economically, it eliminated irrigation pumping costs, reduced idle agricultural land, increased land utilization, and improved farmers’ income. Environmentally, the program restored blocked irrigation channels, rehabilitated previously unproductive land, improved water-flow efficiency, and supported ecosystem preservation. Key success factors included volunteerism, CSR support, multi-stakeholder collaboration, communication technology, local traditions of mutual cooperation, social solidarity, and inclusive gender participation. Conclusion: The FRI program demonstrates that community-based CSR initiatives can simultaneously generate social, economic, and environmental benefits through empowerment-oriented approaches. The findings show how partnerships between corporations and organized communities can create shared value using participatory water management practices. Novelty/Originality of this article: This study provides empirical evidence of the triple bottom line impacts of CSR-supported irrigation management and offers a replicable community-based model for sustainable value creation through people, planet, and profit dimensions.